Distinct Mitochondrial Disturbance in CD4+T and CD8+T Cells From HIV-Infected Patients. (1st February 2017) - Yu, Fengting; Hao, Yu; Zhao, Hongxin; Xiao, Jiang; Han, Ning; Zhang, Yu; Dai, Guorui; Chong, Xuejing; Zeng, Hui; Zhang, Fujie
Abstract : Background: Mitochondrial dysfunction has frequently been found in HIV-infected patients regardless of whether they received antiretroviral therapy (ART). Accumulating evidence suggests that HIV-infected patients exhibit marked changes in mitochondrial membrane potential (MMP), reactive oxygen species (ROS) accumulation, adenosine triphosphate generation, mitochondrial mass (MM), mitochondrial DNA, etc. However, mitochondrial toxicity in CD4 + T and CD8 + T cells caused by different levels of HIV progression and ART is poorly understood. Methods: Blood samples were obtained from 97 ART-naïve HIV-infected patients with different CD4 + T cell counts, 97 nucleoside-reverse transcriptase inhibitors-exposed HIV-infected patients, and 25 HIV-negative subjects. MMP, ROS, and MM in CD4 + T and CD8 + T cells were assessed by flow cytometry. Results: In healthy subjects, the levels of MMP and MM in CD4 + T cells were higher than those in CD8 + T cells. HIV infection led to an increase in MM in CD4 + T and CD8 + T cells, but mainly influenced MMP in CD8 + T cells and ROS accumulation in CD4 + T cells. MM in CD4 + T and CD8 + T cells gradually increased after the loss of CD4 + T cells. Although the dynamic changes in MMP in CD4 + T cells were different from those in CD8 + T cells during highly active ART, MM in both CD4 + T and CD8 + T cells was significantly decreased after 2 years of therapy, but increased again after 3 years. Conclusions: HIV infection and antiretroviral therapy both led to mitochondrial disturbances in CD4 + T cells and CD8 + T cells; however, the abnormal changes in mitochondrial parameters in CD4+T cells were different from those in CD8 + T cells caused by HIV infection and antiretroviral therapy.